Project feasibility analysis : a guide to profitable new ventures - Clifton, David S.; Fyffe, David E. (New York : Wiley, 1977)
This book attempt to present a step-by-step approach for the preparation of project feasibility studies.
"A Wiley-Interscience publication."
Includes bibliographical references and index.
hza 31/01/2019
Loans
Keywords: Project management; Capital investments; Marketing research